Предмет:
МатематикаАвтор:
debreey2 = y1 + d
yn = y1 + (n-1)d
y1 - первый член
d - разница
y3 = y1 + (3-1)d = y1 + 2d
y7 = y1 + (7-1)d = y1 + 6d
y7 - y3 = y1 + 6d - y1 - 2d = 4d
y7 - y3 = -6 - 10 = -16
4d = -16
d = -4
Автор:
federicopierceОтвет: d = -4
Пошаговое объяснение:
По формуле члена арифметической прогрессии
Автор:
noel89Добавить свой ответ
Предмет:
БиологияАвтор:
kayleighrxsaОтветов:
Смотреть
Предмет:
Русский языкАвтор:
celiagrahamОтветов:
Смотреть
Предмет:
Русский языкАвтор:
martínq0gtОтветов:
Смотреть
Предмет:
МатематикаАвтор:
tess66Ответов:
Смотреть